2023
DOI: 10.1519/jsc.0000000000004570
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Training and Associations Between Physical Performance Characteristics and Golf Performance in Female Players: A Systematic Review With Meta-Analysis

Luke Robinson,
Andrew Murray,
Alex Ehlert
et al.

Abstract: Robinson, L, Murray, A, Ehlert, A, Wells, J, Jarvis, P, Turner, A, Glover, D, Coughlan, D, Hembrough, R, and Bishop, C. Effects of physical training and associations between physical performance characteristics and golf performance in female players: A systematic review with meta-analysis. J Strength Cond Res XX(X): 000–000, 2023—The aims of this systematic review were to assess the association between physical performance and measures of golf performance, and the effects of physical training on measures of go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Traditionally, golf is not a sport with a long-standing history of strength and conditioning (S&C) training. However, recent research now indicates a growing awareness of this type of training as part of attempts to improve golf shot performance and over-arching player health [ 7 , 8 , 9 ]. For example, it is now widely accepted that improving strength and power (in both the upper and lower body) is associated with a golfer’s ability to generate increased force production, which is fundamental for achieving the maximum clubhead speed (CHS) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, golf is not a sport with a long-standing history of strength and conditioning (S&C) training. However, recent research now indicates a growing awareness of this type of training as part of attempts to improve golf shot performance and over-arching player health [ 7 , 8 , 9 ]. For example, it is now widely accepted that improving strength and power (in both the upper and lower body) is associated with a golfer’s ability to generate increased force production, which is fundamental for achieving the maximum clubhead speed (CHS) [ 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, Brown et al [ 19 ] reported positive associations between CHS and grip strength on the left hand (in right-handed golfers) ( r = 0.54; p < 0.05), and seated flexibility in both the clockwise and counter-clockwise directions ( r = 0.52–0.71; p < 0.05). With only three studies available in female golfers that relate to the association between S&C training and some surrogate measure of golf performance, it is clear that further research is warranted [ 9 ]. Furthermore, with some questionable assessment methods for physical characteristics selected in previous studies with female players [ 17 , 19 ], there is a need to develop a more robust and comprehensive testing battery to truly elucidate the relationship between physical characteristics and measures of golf performance in female players.…”
Section: Introductionmentioning
confidence: 99%